Implementasi Spasial Kriging Dengan Faktor Dependency Seasonal Time Series - Aniq Atiqi Rohmawati (Indonesia Journal on Computing (Indo-JC), 2016)
Time series analysis has been developed in concepts and theories to accommodate the behavior of the collected data by involving time. The unique feature of time series analysis is the time dependency. In this research, we observed a number of seasonal pets, fire caterpillars, on an oil palm plantation at Block Afdeling-D in Kalimantan. The number of Fire Caterpillars is dependent on time and spatial (location). Fire Caterpillars are seasonal pests on oil palm plantation. In addition, Pearson correlation indicates that the number of Fire Caterpillars is not influenced by the distance among the blocks. We suggests that the disinfection should be done simultaneously to avoid the migration of fire caterpillars. The spreading of fire caterpillars at Block Afdeling-D in Kalimantan is modeled with time series seasonal model, spesifically with ARIMA homoscedastic model. Kriging interpolation was conducted to identify behavior and determine the location Fire Caterpillars involving ARIMA model.Keywords: ARIMA, dependency, Kriging, Fire Caterpillars, variogram